(untitled) (Academicia Globe: Inderscience Research, 2024)
In the article, it is detailed that it is not only the duty of parents, but also the duty of professors and teachers working in higher education institutions to bring up girls as hardworking, knowledgeable, highly cultured, intelligent, wise, family leaders who benefit both the family and the society. highlighted and recommendations developed.